Working apart: Polarisation driven by widening firm gaps and outsourcing - Wouter Zwysen (European Trade Union Institute (ETUI), 2023)
The labour market position of the lower skilled is increasingly under pressure in most high income countries. Their bargaining position is declining under the twin pressures of globalisation and technological change; and they are at risk of losing access to better positions as firms' pay and conditions arrangements increasingly drift apart. These rising between-firm differences partly come about through the increasing separation of lower skilled workers into lower-paying firms with worse conditions, thereby reducing their opportunities further. One mechanism driving this is the process of (domestic) outsourcing where main firms take certain tasks that are seen as non-core out of their payroll, instead purchasing those same tasks from another official employer while being able to retain control. Workers who see their jobs outsourced generally have to work under worse conditions and for lower pay. This paper uses cross-national European data (LFS and SES) along with contextual data to study how the labour market position of lower qualified workers is changing over time and how outsourcing and between-firm segregation is contributing to this gap. I find that (1) domestic outsourcing is increasing over time and leading to greater differences in where the lower and higher qualified work; (2) outsourced workers are working under worse conditions with generally lower wages; and (3) wage gaps by qualifications are increasingly due to between-firm segregation, helped along by this process. However, the process is not universal: it hits harder in sectors with greater technological innovation and can be alleviated by union density and worker representation.
Keywords: 330; Lohnstruktur; Qualifikation; Outsourcing; Ungelernte Arbeitskräfte; Niedriglohn; Arbeitsmarktsegmentation; EU-Staaten